What do our patients know about diabetes mellitus? - (:unkn) unknown (My University, 2000)
Objective: The aim of this descriptive study is to evaluate the knowledge of diabetic and non-diabetic patients of 'diabetes mellitus'. Methods: Eighty-one diabetic and 89 nondiabetic patients who attended different clinics at Marmara University Hospital were included in the study. A questionnaire was used for the evaluation. Results: The mean knowledge score was 78.0 in diabetic patients and 63.0 in the other group; the difference between the scores was statistically significant. There was no statistically significant difference between knowledge and age, sex, marital status, occupation in both groups. However a statistically significant association was found between knowledge and the educational level in the non-diabetic group. 16% of the diabetic patients reported that they had attended a structured educational session or course about diabetes mellitus (DM) in the past. The two main sources of knowledge of the diabetic patients were their physicians and the media, while friends were the main source for the group. There was no association between the knowledge score and duration of the disease in the diabetic group. Conclusion: The results of this study may indicate that health care provider-patient interaction is one of the most important opportunities for patients to obtain knowledge concerning their illness.
Keywords: Autonomy; Diabetes mellitus; Patient education; Patient empowerment